Financial stability and the Fed: evidence from congressional hearings - Arina Wischnewsky; David-Jan Jansen; Matthias Neuenkirch (Center for Economic Studies and ifo Institute (CESifo), 2019)
This paper retraces how financial stability considerations interacted with U.S. monetary policy before and during the Great Recession. Using text-mining techniques, we construct indicators for financial stability sentiment expressed during testimonies of four Federal Reserve Chairs at Congressional hearings. Including these text-based measures adds explanatory power to Taylor-rule models. In particular, negative financial stability sentiment coincided with a more accommodative monetary policy stance than implied by standard Taylor-rule factors, even in the decades before the Great Recession. These findings are consistent with a preference for monetary policy reacting to financial instability rather than acting pre-emptively to a perceived build-up of risks.
Keywords: E52; E58; N12; 330; monetary policy; financial stability; Taylor rule; text mining